Embracing E-learning in Zimbabwe’s Science Teacher Capacity Development Programmes: A Systematic Literature Review - Chikuvadze, Pinias; Permana, Erwin Putera; Makuvire, Claretah; Mugijima, Samuel (Universitas Nusantara PGRI Kediri, 2025)
This paper explores the embracing of e-learning in Zimbabwe's science teacher capacity development programmes, probing the opportunities and challenges. The discussion in this paper grounded in a systematic literature review to provide a holistic view through the use of the PRISMA 2020 checklist ensured transparency and consistency in selecting the 64 sources from databases (DOAJ, DHTE, IBSS, Scielo SA, Scopus and WoS). This provides a comprehensive interrogation of the issue at the centre of discussion. The paper highlights e-learning and how to embrace it in science teacher capacity development. In addition, it outlines approaches used to embrace e-learning in science teacher capacity development. This creates the need to look at how e-learning can enhance accessibility, reduce costs, and improve science teacher capacity development outcomes. However, substantial challenges such as limited access to the internet connection, scarce technological set-up and resistance to transformation from both science teachers were acknowledged. In conclusion, by embracing e-learning in Zimbabwe's science teacher capacity development programmes it creates a platform for promoting education and training. It can be recommended that the stakeholders involved in science teacher capacity development programmes need to establish a strong collaboration such that they can address the identified challenges. Therefore, the use of the right approaches to embracing e-learning in science teacher capacity development programmes can be a game changer in science learning activities.